Photoresponsive prodrug‐dye nanoassembly for in‐situ monitorable cancer therapy - Kaiqi Long; Yifan Wang; Wen Lv; Yang Yang; Shuting Xu; Changyou Zhan; Weiping Wang (Wiley, 2022)
Abstract Photocleavable prodrugs enable controllable drug delivery to target sites modulated by light irradiation. However, the in vivo utility is usually hindered by their insolubility and inefficient delivery. In this study, we report a simple strategy of co‐assembling boron‐dipyrromethene‐chlorambucil prodrug and near‐infrared dye IR783 to fabricate photoresponsive nanoassemblies, which achieved both high prodrug loading capacity (~99%) and efficient light‐triggered prodrug activation. The incorporated IR783 dye not only stabilized the nanoparticles and contributed tumor targeting as usual, but also exhibited degradation after light irradiation and in‐situ monitoring of nanoparticle dissociation by fluorescent imaging. Systemic administration of the nanoparticles and localized light irradiation at tumor sites enabled monitorable and efficient drug release in vivo. Our results demonstrate that such prodrug‐dye co‐assembled nanomedicine is a promising formulation for photoresponsive drug delivery, which would advance the translation of photoresponsive nanomedicines.